(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2019)
N, N′-bis (isatin) diamine schiff base ligands were synthesized by the condensation reaction of Isatin with various diamine (ethane-1,2-diamine, propane-1,3-diamine and hexane-1,6-diamine) in 2:1 molar ratios. These ligands were used to prepare Zr (IV) complexes. Prepared ligands and complexes were characterized by using conductance measurement, FT-IR, UV-Visible and 1HNMR spectroscopy. The presence of FT-IR band for azomethine group supports the formation of ligand. Vibrational bands for Zr←N and Zr←O in complexes signify the coordination through O and N sites of ligands. 1HNMR peak for NH moiety in ligand gets almost disappeared in complex reveals tautomerism of NH with nearby carbonyl oxygen due to the effect of complexation. The absence of peak above 500 nm in the electronic spectra indicates d0 system of zirconium in complexes. The elemental analytical data was analogous to theoretical composition of ligands and complexes. The molar conductance values obtained for the complexes represent their non-electrolytic character. Bangladesh J. Sci. Ind. Res.54(4), 297-306, 2019